Mangrove conservation efforts with the ecotourism development in the Cengkrong Mangrove Ecotourism, Trenggalek District, East Java, Indonesia - Kurniawati, Bella; Sulistyaningrum, Nunik; Nugroho, Gilang Dwi; Sunarto; Kusumaningrum, Lia; Rahawarin, Yohanes Y.; Flores, Andrie Bon; Yap, Chee Kong; Setyawan, Ahmaddwi (Smujo International, 2022)
For mangrove conservation efforts, it is necessary to develop ecotourism so that people can also take advantage of the existence of mangrove forests. Analysis of the role mangrove ecosystem is carried out to develop a mangrove conservation strategy and the concept of sustainable development. This research examined conservation and ecotourism efforts by the community around the Cengkrong Mangrove Ecotourism and social perceptions of ecotourism based on mangrove development. The research was conducted in June 2022 at Mangrove CengkrongEcotourism, Karanggandu Village, Watulimo Sub-district, Trenggalek District, East Java, Indonesia, by conducting interviews with 50 respondents. Data was collected through field observations and interviews with ecotourism administrators and residents around the location. The results of this study indicate that the conservation efforts carried out are protecting, conserving, and utilizing mangroves by seeding, planting, managing, and monitoring mangroves. The POKMASWAS or the Community Monitoring Group manages the Cengkrong Mangrove Ecotourism area. However, the utilization of mangrove forest resources that have economic value by the community around the Cengkrong Mangrove Ecotourism area is still low because it is only limited to the cultivation of crabs,shells, making mangrove syrup, cakes and chips. In addition, the place is quite crowded with tourists. Indeed, area development still lacks preservation, utilization, and conservation for the management, surrounding communities, and tourists. Limited facilities and infrastructure are a challenge for the sustainable development of mangrove ecotourism. In addition, increasing community involvement and collaboration with institutions and the government in mangrove management must also be improved so that all thesurrounding communities can also benefit. With the increasing economic benefits of mangrove ecotourism management, the community around the mangrove forest will participate in maintaining and preserving the mangrove forest ecosystem.